1998
DOI: 10.1007/bf03216744
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic effect of rebamipide on ammonia-induced gastric mucosal hemorrhagic lesion in rats

Abstract: Rebamipide, 2-(4-chlorobenzoylamino)-3-[2(1H)-quinolinone-4-yl]-propionic acid, a novel antipeptic ulcer agent, has been reported to prevent various acute experimental gastric mucosal lesions and to accelerate the healing of chronic ulcers. Therapeutic effect of rebamipide was investigated with regard to the inhibitory effect on xanthine oxidase activity and type conversion of the enzyme which play a profound role in oxygen radicals generation system. Intraperitoneal administration of rebamipide at 60 mg/kg bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2003
2003
2003
2003

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…Interestingly, long-term treatment with ammonia causes atrophic changes in the rat gastric mucosa that are similar to those observed in the human gastric mucosa in patients with chronic HP infections (Kawano et al, 1991;Tsujii et al, 1993). Huh et al (Huh et al, 1998) have also reported that both xanthine oxidase activity and lipid peroxide content increase in ammoniainduced gastric mucosal injury in the rat. Results from the present study are consistent with this observation and demonstrate that intramucosal TBARS levels increase in the gastric mucosa of guinea pigs treated with ammonia.…”
Section: Discussionmentioning
confidence: 79%
“…Interestingly, long-term treatment with ammonia causes atrophic changes in the rat gastric mucosa that are similar to those observed in the human gastric mucosa in patients with chronic HP infections (Kawano et al, 1991;Tsujii et al, 1993). Huh et al (Huh et al, 1998) have also reported that both xanthine oxidase activity and lipid peroxide content increase in ammoniainduced gastric mucosal injury in the rat. Results from the present study are consistent with this observation and demonstrate that intramucosal TBARS levels increase in the gastric mucosa of guinea pigs treated with ammonia.…”
Section: Discussionmentioning
confidence: 79%
“… 30 Similarly, ammonia‐induced gastric mucosal haemorrhagic lesions in rats were improved by the intraperitoneal administration of rebamipide. This reduced the xanthine oxidase activity, lipid peroxide content in ammonia induced haemorrhagic lesion, suggesting that the therapeutic effect of rebamipide on gastric mucosal lesions may in part be due to the inhibitory activity of xanthine oxidase and the conversion rate of the enzyme 31 . Another possible mechanism by which rebamipide may exert its protective effect on the gastric mucosa is through the stimulation of glycosaminoglycan (GAG) synthesis, which may also contribute to the healing process of gastric ulcers 32 .…”
Section: Animal Modelsmentioning
confidence: 99%
“…This reduced the xanthine oxidase activity, lipid peroxide content in ammonia induced haemorrhagic lesion, suggesting that the therapeutic effect of rebamipide on gastric mucosal lesions may in part be due to the inhibitory activity of xanthine oxidase and the conversion rate of the enzyme. 31 Another possible mechanism by which rebamipide may exert its protective effect on the gastric mucosa is through the stimulation of glycosaminoglycan (GAG) synthesis, which may also contribute to the healing process of gastric ulcers. 32 Suzuki et al 33 studied the effects of oral rebamipide in a model of ethanol-induced injury in Mongolian gerbils experimentally infected with H. pylori.…”
Section: Animal Modelsmentioning
confidence: 99%